2018
DOI: 10.1007/s10840-018-0346-y
|View full text |Cite
|
Sign up to set email alerts
|

Dosing of the second-generation cryoballoon using acute time-to-pulmonary vein isolation as an indicator of durable ablation in a canine model

Abstract: In a canine model, effective PV isolation could be found even in the shortest duration dosing cohort (TTE + 60 s). One complication (phrenic nerve injury) was observed in the longest duration dosing group (2 × 180 s). Further studies will be required to correlate these results to a 28-mm cryoballoon (more commonly used in the cryoablation of a human LA); however, to date, this is the first reporting of a successful cryoablation using TTE + 60 s dosing (approximately 90 s total duration of freezing).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…Furthermore, while cryoapplication time to isolation allows titration of the cryoapplication PV reconnection are reported and likely a major contributing factor in AF recurrence. [3][4][5][6] The early determination of durable PVI using the cryoballoon technology will simplify the procedure and likely improve AF ablation success.…”
Section: As Shown Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, while cryoapplication time to isolation allows titration of the cryoapplication PV reconnection are reported and likely a major contributing factor in AF recurrence. [3][4][5][6] The early determination of durable PVI using the cryoballoon technology will simplify the procedure and likely improve AF ablation success.…”
Section: As Shown Inmentioning
confidence: 99%
“…Aryana et al reported that 81% of PVs sleeve potentials where recorded forcing the clinician to apply prolong freeze times to these veins. Furthermore, despite utilizing the time to isolation still, some of the cryoapplications fail to achieve long‐term PV isolation . PV reconnection may reflect tissue stunning as a result of uneven ice formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It quickly became evident that dosing needed to be reduced to minimize collateral injury, especially phrenic nerve palsy and atrial‐esophageal fistula . An alternative time‐to effect (or time‐to‐isolation) approach suggested a single‐freeze for <120 seconds could be adequate under ideal conditions …”
mentioning
confidence: 99%
“…2 An alternative time-to effect (or time-to-isolation) approach suggested a single-freeze for <120 seconds could be adequate under ideal conditions. 3 The continuously evolving target of cryoballoon dosing results in great variation in real-world practice; therefore, the identification and utilization of a physiological end-point is vital. Ablation temperature, acute loss of pulmonary vein (PV) signal, and length of postablation thaw time have all been suggested.…”
mentioning
confidence: 99%